Psychiatric Squele of Sodium Valproate Versus Carbamazipine In Patients with Primary Generalized Epilepsy - Hasan, Zeki Noah; Al Yasiri, Abdul- Rasul; Hassan, Hassan Aziz (AL-Kindy College Medical Journal, 2008)
Background: psychiatric and behavioral side effects are common in patients with epilepsy and it may represent an intrinsic feature of the disease itself or a side effect of the antiepileptic use. Our aim in the present study is to assess the psychiatric side effects of Sodium Valproate and Carbamazipine .as these drugs are the most commonly used antiepileptic drugs in Iraq. Methods: 80 patients with primary generalized epilepsy on Carbamazipine and 50 patients on Sodium Valproate were enrolled in the present study; all the patients were assessed for any psychological disturbances using semi-structural interview based on the tenth edition of the international classification of the diseases(ICD 10) adopted by WHO. Results: Thirty percent of patients taking Sodium Valproate and (9%) of patients taking Carbamazipine were found to have depression while (16%) of patients taking Sodium Valproate and (20 %) of patients taking Carbamazipine were found to have anxiety. There were no reported psychosis, suicidal attempts, cognitive deficit and mania in both groups of patients in the present study. Conclusion: Carbamazipine is preferred to Sodium Valproate when the efficacy of both drugs is comparable.